Pyloric Gland Adenoma of Gallbladder: A Review of Diagnosis and Management. (19th December 2018) - Saei Hamedani, Farid; Garcia-Buitrago, Monica
Abstract : Neoplastic polypoid mucosal lesions of the gallbladder are increasingly being reported in cholecystectomy specimens. However, due to the absence of unified terminology and reporting criteria, the body of scientific evidence on their classification, prognosis, and management is scarce and sometimes controversial. While they have different histomorphologic features (gastric foveolar, gastric pyloric gland, biliary, and intestinal), a significant immunohistochemical overlap exists which highlights their mixed cell lineage with a dominant cell type in each, establishing the subcategory. Because of many shared attributes, intracholecystic papillary-tubular neoplasm (ICPN) has been introduced as an umbrella terminology. ICPNs of the pyloric subtype are lesions larger than 1 cm, as most of the smaller ones are clinically insignificant and represent polypoid hyperplasia rather than a true neoplasm. In this review, we will focus on the pyloric gland adenomas as the most frequent histologic subtype of ICPNs.